Determination of fibernolytic enzyme activities of white rot fungi isolated from oil palm fronds - Mohammad Azri bin Azmi; S. Alias; A.F.M. Azmi; A.A.A. Ghani; M.S. Shahudin; Y.M. Goh; M.M. Noordin; M.T. Yusof; Z. Zunita; H.A. Hassim (Jurnal Ilmu Ternak dan Veteriner, 2016)
Oil palm fronds (OPF) is widely used as the source of roughage for the farm animals. However, the full potential of OPF as animal feed is limited by their high lignin content which limits the rumen microbe’s access to the cellulose and hemicellulose. White rot fungi (WRF) are a group of fungi belonging to basidiomycete phylum and are commonly found in decaying woody plant. They possess the ability to degrade lignin. This experiment aims to identify the phylum of the best lignin decaying fungi based on their enzymes activity. In this experiment, 11 fungi species were isolated from decaying oil palm fronds. They are labelled as WR1, WR 2, WR3, WR4, WR5, WR6, WR7, WR8, WR9, WR10 and WR11. Their fibernolytic enzyme activities which includes laccase, manganese peroxidase, lignin peroxidase, avicelase, carboxylmethylcellulase and xylanase are analysed using the solid state fermentation method. It is was found that 5 fungi species which are the WR1, WR2, WR4, WR7 and WR10 produced the highest ratio of lignin degrading enzyme to cellulose and hemicellulose degrading enzyme. The fungi are then analysed under microscope to determine the phylum of the fungi. From the observation, the fungi are identified to belong to the phylum basidiomycetes due to presence of clamp connection.